Navigating Without a Compass: A Qualitative Case Study on the Experiences of Postgraduate Students with Unstructured or Absent Supervision (Student's Journal of Health Research Africa, 2025)
BackgroundPostgraduate supervision is critical to academic success and student well-being in higher education. However, many students encounter challenges due to unstructured, inconsistent, or absent supervision, resulting in research delays, emotional distress, and reduced academic confidence. This study explores the lived experiences of postgraduate students navigating their academic journeys without adequate supervisory support.MethodsA qualitative case study design was employed to gain an in-depth understanding of postgraduate supervision experiences. The study was conducted at a public South African university, with a purposive sample of 20 participants comprising 15 master’s students and 5 doctoral students across disciplines including science, education, and humanities. Data were collected through 12 semi-structured interviews and two focus group discussions involving 8 participants. Thematic analysis, guided by Braun and Clarke’s six-step framework, was used to identify key themes related to supervisory relationships, emotional well-being, institutional support, and coping strategies.ResultsThe findings reveal that 85% of participants experienced irregular communication, lack of timely feedback, and minimal academic guidance. These deficiencies often led to confusion, demotivation, academic isolation, and project delays. Students with access to informal mentorship or peer networks exhibited greater resilience. Institutional supervision policies were often poorly communicated or inconsistently enforced, compounding the challenges faced by students.ConclusionUnstructured or absent postgraduate supervision detrimentally affects both academic progress and mental health. Inconsistent supervisory practices foster environments of uncertainty and frustration, frequently pushing students toward informal support systems.RecommendationsHigher education institutions should establish and enforce clear supervision policies across faculties. Supervisor training and performance monitoring must be institutionalized. Furthermore, accessible grievance channels, formal mentorship programmes, and peer support networks should be integrated to bridge supervisory gaps and promote student success.